Kapasitas Kerja dan Efisiensi Hand Traktor untuk Pengolahan Tanah di Lahan Rawa Pasang Surut Tipe C dan Lahan Irigasi Setengah Teknis di Kalimantan Selatan - Indya Dewi; Bambang Fredrickus Langai; Bima Ugi Supriyanto (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Dewi I, Langai FB, Supriyanto UB. 2020. Work capacity and efficiency of hand tractors for soil processing in tidal swamp lands type C and semi-technical irrigation in South Kalimantan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The working capacity of soil processing machines is very important to test in order to determine the performance of these tools, considering that so far tractor assistance is top down not bottom up, so that tractor assistance designed in Java, which generally has alluvial lands, needs to be tested for its performance in South Kalimantan which generally dominated by swamps. The purpose of this study was to describe the performance of the hand tractor in tidal swamp land type C and semi-technical irrigation. The method used in this research is an experimental method without design and presented descriptively. The parameters tested are actual working capacity, theoretical working capacity, work efficiency, fuel oil consumption. The results showed that the actual working capacity and the theoretical working capacity of the hand tractor in tidal swamp type C and semi-technical irrigated land were 0.159 ha/hour, 0.122 ha/hour, 0.364 ha/hour and 0.371 ha/hour, respectively. Work efficiency is 43.7% and 32.9%. Consumption of fuel oil 0.48 liters and 0.71 liters.